Strategi Kepala Sekolah dalam Meningkatkan Kedisiplinan Guru di SMA Negeri 11 Muaro Jambi - Oji Nur Aslam; Mohamad Muspawi; Mulyadi (Al-fahim : Jurnal Manajemen Pendidikan Islam, 2023)
The purpose of this study is to describe the strategies used by school principals in their efforts to improve teacher discipline. The place of this research is located at SMA Negeri 11, Muaro Jambi Regency, Jambi Province. The method used in this study is to use a qualitative descriptive method with a phenomenological approach. Data collection techniques used in this study are by observation and interviews. Activities carried out in data analysis begin with data reduction, data display, and the last is drawing conclusions or data verification. The results obtained from this study are that school principals carry out various strategies in an effort to improve teacher discipline, namely by providing rewards and punishments, carrying out new innovations, having high motivation, providing direction and coaching, and taking a persuasive approach. The conclusion from this study is that the principal finds there are obstacles for teachers to implement discipline in schools, including a lack of teacher motivation and awareness for discipline so that the principal carries out a special strategy in solving this including providing punishment, carrying out new innovations and providing coaching and warnings for teachers who are not yet disciplined.